The Pressor Response to the Drinking of Cold Water and Cold Carbonated Water in Healthy Younger and Older Adults - Kubota, Satoshi; Endo, Yutaka; Kubota, Mitsue; Miyazaki, Hiroko; Shigemasa, Tomohiko (Frontiers in Neurology, 2022)
Abstract Purpose: Water drinking has been proposed for the treatment of orthostatic hypotension because it can increase blood pressure in patients. This study aimed to investigate whether drinking water with a cold or carbonation stimulus would cause a more effective pressor response, and whether it would be greater in older than in younger adults. Methods: We assessed blood pressure and heart rate from noninvasive arterial pressure (a volume-clamp method) and type II electrocardiography in 13 healthy young adults (6 females, 7 males; mean age, 19.9 ± 1.1 years) and nine healthy older adults (all females; mean age, 71.4 ± 4.2 years) who drank 200 mL of cold, cold carbonated, and room temperature water. Results: The pressor response to the drinking of cold and cold carbonated water was greater than that to room temperature water in both younger and older participants (p<0.05; changes in systolic blood pressure of room temperature water, cold water and cold carbonated water in young: 15.31±9.66, 22.56±11.51 and 32.6±17.98 mmHg, respectively; changes in systolic blood pressure of room temperature water, cold water and cold carbonated water in elderly: 21.84±14.31, 41.53±19.82 and 48.16±16.77 mmHg, respectively). In addition, the pressor response to cold and cold carbonated water was persistent during the recovery period by about 5~10 mmHg (p<0.05). Furthermore, the pressor response during the drinking and recovery periods was greater in the older than in the younger participants (p<0.05). Conclusion: Our data suggest that even smaller amounts of water are able to elicit a sustained pressor response, in particular if the water is cold and carbonated. We speculate that the pressor effect may render cold and carbonated water an appropriate first aid method against certain forms of acute hypotension.